Circular economy supply chain for sustainable development goals (SDGS): A review and future opportunities - Kurniawan, Ivan; Fernando, Yudi (Penerbit Universiti Malaysia Pahang, 2023)
The issue of sustainability has escalated over the years as the growing concern of world resources that have begun to deplete. Hence, the United Nations (UN) adopted the sustainability 2030 agenda with 17 sustainable development goals (SDGs) to pursue economic, environmental, and social objectives. One of the most prominent concepts to achieve sustainability is circular economy supply chain (CESC). The basic idea of CESC is a system that aims to eliminate waste and preserves natural resources by keeping materials in use and a regenerative natural system. Therefore, the purpose of this paper is to examine the connection between CESC and SDGs as well as the opportunities for research in the future. A systematic literature review on the CESC for SDGs is carried out. There is a significant increase in studies associated with the implementation of CESC to achieve SDGs. The results show that CESC contributes significantly to SDG 2, SDG 8, and SDG 12. Another finding is that technologies could assist CESC practices. CESC implementation for achieving SDGs is not only for big enterprises but also for small and medium enterprises (SMEs). Discussions related to social aspects are less often carried out than from economic and environmental aspects. Future opportunities have been identified for four industrial sectors: manufacturing, agriculture, waste management, and natural resources.